Lower dose of ATG combined with basiliximab for haploidentical hematopoietic stem cell transplantation is associated with effective control of GVHD and less CMV viremia - Huang, Zhenli; Yan, Han; Teng, Yao; Shi, Wei; Xia, Linghui (Frontiers in Immunology, 2022)
Currently, the graft-versus-host disease (GVHD) prophylaxis consists of an immunosuppressive therapy mainly based on antithymocyte globulin (ATG) or post-transplant cyclophosphamide (PTCy). GVHD remains a major complication and limitation to successful allogeneic haploidentical hematopoietic stem cell transplantation (haplo‐HSCT). We modified the ATG-based GVHD prophylaxis with the addition of basiliximab in the setting of haplo-HSCT and attempted to explore the appropriate dosages. We conducted a retrospective analysis of 239 patients with intermediate- or high-risk hematologic malignancies who received haplo-HSCT with unmanipulated peripheral blood stem cells combined or not with bone marrow. All patients received the same GVHD prophylaxis consisting of the combination of methotrexate, cyclosporine or tacrolimus, mycofenolate-mofetil, and basiliximab with different doses of ATG (5-9mg/kg). With a median time of 11 days (range, 7-40 days), the rate of neutrophil engraftment was 96.65%. The 100-day cumulative incidences (CIs) of grade Ⅱ–Ⅳ and Ⅲ–Ⅳ aGVHD were 15.8±2.5% and 5.0±1.5%, while the 2-year CIs of total cGVHD and extensive cGVHD were 9.8±2.2% and 4.1 ± 1.5%, respectively. The 3-year CIs of treatment-related mortality (TRM), relapse, overall survival (OS), and disease-free survival (DFS) were 14.6±2.6%, 28.1±3.4%, 60.9±3.4%, 57.3±3.4%, respectively. Furthermore, the impact of the reduction of the ATG dose to 6 mg/kg or less in combination with basiliximab on GVHD prevention and transplant outcomes among patients was analyzed. Compared to higher dose of ATG(>6mg/kg), lower dose of ATG (≤6mg/kg) was associated with a significant reduced risk of CMV viremia (52.38% vs 79.35%, P<0.001), while the incidences of aGVHD and cGVHD were similar between the two dose levels. No significant effect was found with regard to the risk of relapse, TRM, and OS. ATG combined with basiliximab could prevent GVHD efficiently and safely. The optimal scheme of using this combined regimen of ATG and basiliximab is that administration of lower dose ATG (≤6mg/kg), which seems to be more appropriate for balancing infection control and GVHD prophylaxis.